Identification and classification of risk factors for human-robot collaboration from a system-wide perspective. (January 2022) - Berx, Nicole; Decré, Wilm; Morag, Ido; Chemweno, Peter; Pintelon, Liliane
Highlights: Safety for collaborative robots is mainly considered from a technical perspective. A system-wide perspective allows to consider other and new risk factors. Risk Factors for Human-Robot Collaboration can be classified in five classes. Abstract: Industry 4.0 systems in general and advanced manufacturing systems such as collaborative robots, in particular, are characterized by a high level of complexity leading to new safety concerns. Safety, specifically for collaborative robots, has been mainly addressed from a technical perspective, to safeguard the physical safety of the operator. Concerns have been raised regarding less focus in Industry 4.0 literature on how other factors, such as psychosocial can produce safety-related risks for the operator in human-robot collaboration. This paper identifies and classifies the risk factors in a human-robot collaboration that have been described in research papers in the last decade. The resulting five classes constitute dimensions that will be used as preliminary building blocks for a safety evaluation framework to be developed in the next step. By evaluating the resulting classes with the underlying dimensions of contemporary socio-technical thinking, this paper demonstrates that these five classes offer a comprehensive, system-wide perspective including risk factors beyond technological considerations. Topics emerging from new risks related to the impact of working with collaborative robots, such as psychosocial, ethical, and cyber risk factors will need to be taken into account in the risk factors that are important to identify, assess and mitigate before working with collaborative robots. Operator involvement and participation, especially throughout the risk assessment and mitigation cycle are recommended as new areas of attention in human-robot collaboration. Going forward, one challenge will be the agility and adaptability of legislation to at least keep track of risk factors emerging from continuously changing technologies and to translate them into practically applicable tools for enterprises and design engineers implementing collaborative applications. Another key challenge will be the measurement of the new emerging and sometimes less technological risks.